Effect of Gelatin and Iota-Caragenan (Eucheuma spinosum) on the Quality of Green Cincau (Premna oblongifolia Merr) Jelly - Julfi Restu Amelia; Aura Putri Aryanti (The University of Lampung, 2026)
Green cincau (Premna oblogifolia Merr) can form gel, but it is fragile and easily syneresis, so gelatine is needed as another gel-forming material. However, the addition of gelatine with high concentration causes hard texture, therefore iota carrageenan as an alternative gel-forming material is substituted. The purpose of this study was to determine proper ratio of gelatine and iota-carrageenan concentrations for the quality of green grass jelly products. The experiment was arranged in completely randomized design (CRD) with 5 ratios of Gelatine to Iota Carrageenan, namely P1 (10%:0%), P2 (7%:3%), P3 (5%:5%), P4 (3%:7%) and P5 (0%:10%). Data was analyzed using ANOVA followed by HSD test at α = 0.05 for texture test, water content, ash content, antioxidant activity value, and organoleptic test. Results showed that the best treatment for green cincau jelly was treatment P3 with gel strength at hardness parameters of 2200.23 gf, springiness 0.96%, chewiness 1911.30 gf, and gumminess 2111.98 gf due to the interaction between gelatine and iota carrageenan. The water content was 47.28%, ash content was 1.06%, antioxidant content was 374.83 ppm, hedonic values for all parameters were in the range of 4 (taste) and 5 (colour, aroma, texture) and the results of the number of yeast molds <1×102 colonies/ml.